Tricho-odonto-onycho-dermal dysplasia and WNT10A mutations - Kantaputra P. (Wiley-Liss Inc., 2014)
We report on three novel (IVS2+1G>A splice site, c.1066G>T, and c.1039G>T, and one previously reported (c.637G>A) WNT10A mutations in three patients affected with odonto-onycho-dermal dysplasia (OODD; OMIM 275980). OODD is a rare form of autosomal recessive ectodermal dysplasia involving hair, teeth, nails, and skin, characterized by hypodontia (tooth agenesis), smooth tongue with marked reduction of filiform and fungiform papillae, nail dysplasia, dry skin, palmoplantar keratoderma, and hyperhidrosis of palms and soles. The novel IVS+1G>A splice site mutation is predicted to cause significant protein alteration. The other novel mutations we found including c.1066G>T and c.1039G>T are predicted to cause p.Gly356Cys and p.Glu347X, respectively. Barrel-shaped mandibular incisors and severe hypodontia appear to be associated with homozygous or compound heterozygous mutations of WNT10A. The name "tricho-odonto-onycho-dermal dysplasia" is suggested to replace "odonto-onycho-dermal dysplasia" because hair anomalies including hypotrichosis and slow-growing hair have been reported in numerous reported patients with this syndrome. © 2014 Wiley Periodicals, Inc.